An Objective Computational Method to Quantify Ankle Osteoarthritis From Low-Dose Weightbearing Computed Tomography. Issue 3 (August 2022) - Tazegul, Tutku E.; Anderson, Donald D.; Barbachan Mansur, Nacime S.; Kajimura Chinelati, Rogerio Marcio; Iehl, Caleb; VandeLune, Christian; Ahrenholz, Samuel; Lalevee, Matthieu; de Cesar Netto, Cesar
Background: The treatment of ankle osteoarthritis (OA) varies depending on the severity and distribution of the associated joint degeneration. Disease staging is typically based on subjective grading of appearance on conventional plain radiographs, with reported subpar reproducibility and reliability. The purpose of this study was to develop and describe computational methods to objectively quantify radiographic changes associated with ankle OA apparent on low-dose weightbearing CT (WBCT). Methods: Two patients with ankle OA and 1 healthy control who had all undergone WBCT of the foot and ankle were analyzed. The severity of OA in the ankle of each patient was scored using the Kellgren-Lawrence (KL) classification using plain radiographs. For each ankle, a volume of interest (VOI) was centered on the tibiotalar joint. Initial computation analysis used WBCT image intensity (Hounsfield units [HU]) profiles along lines perpendicular to the subchondral bone/cartilage interface of the distal tibia extending across the entire VOI. Graphical plots of the HU distributions were generated and recorded for each line. These plots were then used to calculate the joint space width (JSW) and HU contrast. Results: The average JSW was 3.89 mm for the control ankle, 3.06 mm for mild arthritis (KL 2), and 1.57 mm for severe arthritis (KL 4). The average HU contrast was 72.31 for control, 62.69 for mild arthritis, and 33.98 for severe arthritis. The use of 4 projections at different locations throughout the joint allowed us to visualize specifically which quadrants have reduced joint space width and contrast. Conclusion: In this technique report, we describe a novel methodology for objective quantitative assessment of OA using JSW and HU contrast. Clinical Relevance: Objective, software-based measurements are generally more reliable than subjective qualitative evaluations. This method may offer a starting point for the development of a more robust OA classification system or deeper understanding of the pathogenesis and response to ankle OA treatment.